Pelatihan Pengawetan dan Pembuatan Kulit Perkamen untuk Pemanfaatan Kulit Kelinci pada Perkumpulan Peternak Kelinci Bantul - Rahmawati, Atiqa; Ajie, Baskoro; Wibowo, R. Lukas Martindro Satrio Ari; Yuliatmo, Ragil; Wulandari, Dwi; Abdullah, Sofwan Siddiq; Darmawati, Entien (Universitas Sebelas Maret, 2022)
Training on Preservation and Parchment Skins Making for Utilization of Rabbit Skins at Bantul Rabbit Breeders Group. The waste product of rabbit breeders includes rabbit skin. Most rabbit breeders require assistance in processing and utilizing rabbit skin waste. This activity aims to help rabbit breeders get more skilled at recognizing the potential of rabbit skins and developing products from them. Due to this, rabbit skin may have a higher commercial worth. The method used in this activity is participatory counseling, which involves the participants directly in the training activities. The activity is accomplished in three steps: collaboration with the rabbit breeders' group and the neighborhood's head; implementation of the rabbit breeders' training program; and evaluation. The activity results showed that the participants were enthusiastic, interested and provided favorable comments throughout the program. The evaluation results have shown that the instructors scored 85,62 on a scale of 0 to 100 for their performance. This condition shows that the participants can well receive the delivery of material by the instructor. In the evaluation of the organizers as a whole, they got an average of 4.05 (scale 0–5). The results of the average pretest and posttest scores increased from 68 to 77, or around 13.24% of the value. The materials provided throughout training are helpful for rabbit breeders in terms of maintaining rabbit skin and employing rabbit skin in the production of parchment skin.